2007
DOI: 10.1111/j.1432-2277.2006.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of indoleamine 2,3-dioxygenase in transplantation

Abstract: Summary Indoleamine 2,3‐dioxygenase (IDO), by enzymatic tryptophan degradation, has recently been proposed to have profound immunoregulatory activity. By most recent findings IDO induction follows reverse signaling of cytotoxic T‐lymphocyte antigen‐4 (CTLA‐4) to its ligands CD80/86 and acts as a counter‐regulatory mechanism to T‐cell stimulation. With regard to transplantation, experimental evidence suggests that IDO has the potential to down‐regulate allo‐responses of T cells in vitro and to promote tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 73 publications
(97 reference statements)
4
42
0
Order By: Relevance
“…This phenomenon is quite unusual [16], since IDO is often regarded as a feedback mechanism to inflammation, which may be indicated by proinflammatory cytokines [6,8]. However, this finding corroborates our concept that proinflammatory DC cytokine production and IDO induction are separate processes [6].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This phenomenon is quite unusual [16], since IDO is often regarded as a feedback mechanism to inflammation, which may be indicated by proinflammatory cytokines [6,8]. However, this finding corroborates our concept that proinflammatory DC cytokine production and IDO induction are separate processes [6].…”
Section: Discussionsupporting
confidence: 86%
“…First, the T-cell suppressive effect of IDO is dependent on the explicit presence of IDO competence; in other words, once IDO-competent DCs are replaced by IDO-incompetent APCs, T-cell proliferation is recovered. This observation fits into a concept, in which IDO despite essentially participating in immunoregulation does not induce sustained down-regulation of immune reactivity [8], that is IDO-mediated T-cell inhibition is rapidly reversible once IDO activity ceases. Second, T cells after stimulation with PGE 2 -matured DCs are predisposed for production of enhanced levels of multifaceted, cytokines polarizing Th1, Th2, and Th17 cells.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…6 It has been suggested that, due to its immunoregulatory effects, IDO may actively participate in down-regulating allogeneic immune responses in transplantation. 7 Our research group has provided compelling evidence in support of the fact that the expression of IDO in by-stander fibroblasts through IDO genetic modification or interferon-␥ treatment suppresses immune cell proliferation. 8 -13 In addition, we also have shown that, by an unknown mechanism, only immune but not primary skin cells are sensitive to the IDO suppressive effect.…”
mentioning
confidence: 97%
“…Attempts have been made also to apply DCs transduced with constructs for both IL-10 and TGF-, which led to increased graft survival compared to single cytokine-expressing DCs (Gorczynski, Bransom et al 2000). Several experimental data confirmed an essential role of IDO and DCs in immunoregulation of allo-responses (Hainz, Jurgens et al 2007;Cook, Bickerstaff et al 2008). In a rat kidney transplantation model, allograft tolerance was induced by administration of an anti-CD28 Ab (Haspot, Seveno et al 2005).…”
Section: Tdcs In Transplantationmentioning
confidence: 99%